Motivational Counseling to Reduce Sedentary Behaviors and Depressive Symptoms and Improve Health-Related Quality of Life Among Women With Metabolic Syndrome. Issue 4 (July 2019) - Chiang, Li-Chi; Heitkemper, Margaret McLean; Chiang, Shang-Lin; Tzeng, Wen-Chii; Lee, Meei-Shyuan; Hung, Yi-Jen; Lin, Chia-Huei
Abstract : Background: Motivational interviewing, as a counseling approach, could promote not only behavioral changes but also individuals' psychological adaptation. Previous studies provide evidence that motivational interviewing focused on increasing physical activity decreases the risk of metabolic syndrome in women. Its effects on sedentary behaviors, depressive symptoms, and health-related quality of life (HRQL) remain unknown. Objectives: The aim of this study was to evaluate whether a 12-week motivational counseling program reduces sedentary behaviors and depressive symptoms and improves HRQL in Taiwanese women. Methods: A randomized controlled study was conducted. Participants (n = 115) were randomly assigned into 3 groups: experimental group (received a brochure on lifestyle modification combined with 12 weeks of motivational counseling), comparison group (received a lifestyle modification brochure), and usual care group (UCG). Outcome variables were measured at baseline and at 12 weeks post intervention by the International Physical Activity Questionnaire, Beck Depression Inventory, and Medical Outcomes Short Form-36 Health Survey. Generalized estimating equations were applied to analyze the intervention effects of groups by interaction of group and time. Results: Women in the experimental group not only reduced ( P < .001) weekly sitting time by 374 minutes but also decreased ( P < .05) depressive symptoms, as well as had greater overall HRQL including 8 subscales as compared with the UCG. As compared with the UCG, the women in the comparison group had no change in sedentary behaviors, but they had reduced depressive symptoms and improvement on some HRQL subscales. Conclusions: Motivational counseling that incorporates behavioral change principles is effective in reducing sedentary behaviors and depressive symptoms and improving HRQL for women with metabolic syndrome.